Investigation of the Nature of Degradation Products of Dental Luting Cements by Atomic Absorption Spectrophotometry - YANIKOGLU, NURAN; BAYINDIR, FUNDA; MELTEM COLAK, K.; OZLI, HATICE (Asian Journal of Chemistry, 2010)
The aim of this study was to examine the nature of degradation products of dental luting cements, life base, temp bond, carboxylate cement and durelon. Disintegration studies were done using standard cement disks (20 mm in diameter × 1.5 mm thick). The cement disks were prepared according to the manufacturer's recommendations and immersed in 50 mL of water for 7 d. Co, Cu, Cr and Zn in the test solutions were determined by atomic absorption spectrophotometry. In the temp bond cement (ZnO eugenol), Zn is major constituent of the cement. But only minor constituent of the leachate; conversely, Co and Cu, only minor constituents of the cement. Zn and Co are major constituents of the durelon and carboxylate cements. Carboxylate cement was second lowest in loss of material in this study.